PANDANGAN FUQAHA TETANG KEWARISAN ANAK DARI HASIL PERKAWINAN BEDA AGAMA MENURUT KUHP PERDATA DAN KOMPILASI HUKUM ISLAM - Khalid Khalid (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
Jumhur fuqaha (Malikiyah, Syafi'iyah, and Hanabilah are valid) argue that Muslims should not accept the inheritance of apostates because Muslims do not pass on to unbelievers and apostates belong to unbelievers. Whereas according to the Hanafi school the wealth of apostate people can be inherited to Muslim relatives because Islam is a high religion. When viewed from the point of view of Islamic inheritance law, children born from interfaith marriages do not have the right to obtain inheritance if they are not religious as heirs, in this case the heirs are Muslim. However, if the heir is Muslim while the heirs are not Muslim (non-Muslim), then they still have the right to inherit each other. This is based on the relationship of blood between the testator and heirs. Therefore, to not give exception to children who are of different faiths with their parents, in this case their parents are Muslim and their children are non-Muslim. The government issued a legal stipulation stipulated in the jurisdiction of the Supreme Court of the Republic of Indonesia. Number: 368 K / AG / 1995.